Analisis Pengaruh Kebijakan Dividen Terhadap Nilai Perusahaan - Nirawati, Lia; Samsudin, Acep; Puteri Pradanti, Alsya; Widya Ayu, Aisyah; Aura Jahzy, Cantika; Dwi Isma Saputri, Intan; Prisichella, Azzahra (CV. Lafadz Jaya, 2022)
This journal contains the company's dividend policy in banking companies listed on the Indonesia Stock Exchange. The objects surveyed are banking companies listed on the IDX between 2012 and 2016 using a targeted sampling method. The sample criteria taken were banks listed on the Indonesia Stock Exchange in the period 2012 to 2016, and financial reporting distributing dividends for the period 2012 to 2016, which finally obtained a sample of 30 companies. The data source is obtained from the annual financial statements of banking companies through access to the official website of the Indonesia Stock Exchange. The results showed that dividend policy had a negative impact on firm value and not significant on firm value.